UPAYA PENINGKATAN PEMBELAJARAN SEPAK TAKRAW MENGGUNAKAN VARIASI BOLA PADA SISWA KELAS V SD NEGERI SEMBUNGHARJO 1 KECAMATAN PULOKULON KABUPATEN GROBOGAN (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is Â to determine Improved Learning through Variation Takraw Soccer ball in the fifth grade students of SD Negeri 1 Sembungharjo District Pulokulon Grobogan. The method used in this study is action research with the subject of this study is the fifth grade students of SD Negeri 1 Sembungharjo which consists of 40 students. The research was conducted in two cycles of action. The first cycle was held on Thursday, May 23, 2013 and the second cycle was held on May 28, 2013. The data obtained were analyzed with the existing calculation formula. Results obtained from the first cycle average percentage of 66.67% cognitive, affective aspects average 56.50%, average 64.30% with psychomotor aspects of KKM to be achieved is 65%. While the results of the second cycle obtained an average percentage of 91% cognitive, affective average of 91%, average 74.33% with psychomotor aspects of KKM to be achieved is 65%. Thus the conclusion that can be drawn using a variety of learning sepak takraw plastic ball and rubber ball in Physical Education and Health Sport can improve learning sepak takraw fifth grade students of SD Negeri 1 Sembungharjo District Pulokulon Grobogan.